The relationship between IDH, P53 mutations, MGMT methylation with characteristics in high grade glioma patients - Duc Anh Tran; Ba Van Nguyen; Bac Thanh Nguyen; Hoe Van Vu; Lien Duc Nguyen (Revista Cubana de Medicina Militar)
Introduction: Some gene mutations in high grade glioma patients have many implications in prognosis and treatment response. Objectives: To describe the characteristics and associations of IDH, TP53 gene mutations and MGMT methylation status with some characteristics and treatment response in patients with high grade glioma. Methods: A descriptive, prospective, uncontrolled study was conducted, in 52 patients with high-grade glioma. Research variables include age, sex, Karnofsky score, the rate of IDH, P53 mutation, MGMT methylation; the relationship between genes mutation with some characteristics and response to treatment according to the RECIST classification. Results: For IDH gene mutation, grade III patients (23.1%) have a higher positive rate than grade IV (11.5 %); for P53 gene mutation, grade III patients (55.6 %) have a higher positive rate than grade IV (44.1 %); the rate of MGMT promoter methylation occurred in the study group of patients with the rate of 42.3 %. There is a relationship between IDH gene mutation with pathological results and malignancy in studied patients. Patients with the mutant expression of the IDH gene, p53, MGMT methylation status had better RECIST responses than patients without these expressions. Conclusion: High-grade glioma mainly occurs in men, over 40 years old. The presence of mutations in IDH, P53 genes, and MGMT methylation status was a beneficial factor for treatment response as assessed by RECIST.